Molecular Systematics of Redband Trout from Genome-Wide DNA Sequencing Substantiates the Description of a New Taxon (Salmonidae: Oncorhynchus mykiss calisulat) from the McCloud River - Campbell, Matthew A.; Habibi, Ensieh; Auringer, Grace; Stephens, Molly; Rodzen, Jeff; Conway, Kevin W.; Finger, Amanda J. (Zootaxa, 2023)
Rainbow Trout, Oncorhynchus mykiss, exhibit high levels of phenotypic diversity leading to the recognition of numerous subspecies. A major distinction among Rainbow Trout subspecies exists between Coastal Rainbow Trout (O. m. irideus), which occurs west of the Cascade and Sierra Nevada mountain ranges, and interior Redband Trout (O. mykiss sspp.), largely distributed to the east. Interior Redband Trout are composed of three primary lineages and can share various outward, anatomical or physiological characteristics that are often symplesiomorphies or examples of convergence. We examine high-throughput DNA sequence data from Sacramento Redband Trout O. m. stonei from the Upper Pit and Upper McCloud Rivers along with representatives of Rainbow Trout and Golden Trout lineages to clarify the composition and relationships of the Sacramento Redband Trout. We find O. m. stonei to be polyphyletic, divided between populations in the Pit River and the Upper McCloud River. Redband Trout obtained from the Pit River are most-closely related to Great Basin Redband Trout O. m. newberrii and to fish of the Warner Lakes Basin and Surprise Valley within the O. m. newberrii lineage. The type specimen of O. m. stonei, collected from the Lower McCloud River, is phenotypically similar to Great Basin Redband Trout. We find as well that the isolated populations of trout in the Upper McCloud River Basin represent a lineage of Rainbow Trout now restricted to that region, are monophyletic and are not most closely related to the interior Redband Trout lineages of O. m. newberrii or O. m. gairdnerii. Furthermore, they are not represented by the type specimens of O. m. stonei or O. m. shasta. Consequently, we formally describe the McCloud River Redband Trout O. mykiss calisulat, new subspecies.